Webbed Connectivities : The Imperial Sociology of Sex, Gender, and Sexuality - Patil, Vrushali (Book collections on Project MUSE., 2022)
"Webbed Connectivities offers a global historical sociology that reembeds the United States within histories of empire, situating the emergence of northern and U.S.-based concepts and frameworks squarely within these histories. It explores the theoretical spaces that spotlighting imperial hierarchies within knowledge production might open, including making productive and essential connections across sites of the global south and north"--